Effects of Glyoxylic Acid on Metabolism and Ripening of ‘Rocha’ Pears Treated with 1-MCP - Cindy Dias; Clara Sousa; Marta W. Vasconcelos; António Ferrante; Manuela Pintado (Horticulturae)
The application of 1-methylcyclopropene (1-MCP) is widely used to extend the storage life of climacteric fruits, such as ‘Rocha’ pears. However, the suppression of ethylene’s action by 1-MCP often results in excessive ripening delay, compromising fruit quality and consumer acceptance. In this study, we investigated the potential of glyoxylic acid (GLA) to counteract the effects of 1-MCP and promote ripening. To evaluate this, ‘Rocha’ pears treated with 1-MCP were exposed to 3% (m/v) GLA and stored at 20 ± 2 °C for 15 days. Typical ripening indicators, such as firmness, skin color, ethylene production, respiration rate, volatile organic compounds (VOCs), sugars, and the activity of ethylene biosynthetic enzymes, were measured. Our results indicate that GLA did not induce significant effects on the ripening response, as ethylene production remained comparable to that of the control. Consequently, no significant changes in firmness, skin yellowing, or sugar content were observed in the GLA-treated pears. However, GLA significantly increased respiration rates (approximately 57%) and induced higher emissions of stress-associated VOCs, including hexanal, (E)-2-hexenal, and ethanol. This suggests that GLA may influence metabolic pathways related to energy metabolism and redox homeostasis without necessarily triggering ethylene-induced ripening. This study provides new insights into the interactions between GLA, 1-MCP, and fruit development, contributing to the development of alternative strategies to manage the effects of 1-MCP in ‘Rocha’ pear storage.